(untitled) (Research, Society and Development, 2021)
This study aimed to analyze the role of the companion in the process of humanization of childbirth and identify the factors that hinder their presence. This is a descriptive and exploratory qualitative research. The sample consisted of 14 users of a Basic Health Unit selected by convenience who had children in the municipality of Aracaju. For data collection an interview was conducted through a semi-structured questionnaire. It was evident that 87.7% of respondents would like to have the presence of a companion, however, the majority (58.3%) did not have the right assured. Interventions aimed at calming the parturient are measures that allow calmness and safety, making the time of childbirth more gentle and special. Among these measures are: the dialogue carried out by the companion, drug therapy to relieve symptoms, use of the Swiss ball as a technique to minimize tension, reduce anxiety and discomfort for women who are in labor. It is understood that a law that ensures this right is not enough for its practice to be implemented, with the need for awareness among the population, professionals and managers.